PP02 Testing a universal perception of disease and disability hypothesis in an irish population. (31st August 2015) - Travers, J; Holloway, P
Abstract : Background: The most recent Global Burden of Disease (GBD) study indicates that the burden of diseases is perceived similarly by individuals throughout the world, despite major differences in culture, geographic location and socio-economic status. Such similarity in perception raises the possibility that there might be universality in how diseases and disabilities are viewed by all people. This study answers the call from the GBD team to test this universality hypothesis in different populations. Methods: We undertook a survey to determine if a universal perception of disease and disability could be identified in an Irish population. We asked 50 participants to weigh 60 distinct health conditions on a scale of 0 ('no health loss') to 10 ('health loss equivalent to death'). We also recorded demographic information on age, gender and urban or rural residence. The health conditions were selected from the most recent GBD survey. An online survey via social media enabled convenience sampling. Participation was voluntary and all data was recorded on an anonymous basis. We calculated the mean weighting of each condition for total sample size and by gender. Standard deviation was calculated with 95% confidence interval to determine reliability. The coefficient of variation was calculated to show the dispersion of frequency distribution in relation to the mean. The Pearson product momentum correlation coefficient was calculated to measure the strength of association between the Irish and GBD results. Data was analysed using Microsoft excel. Results: The highest weighted conditions were severe stroke (8.70), metastatic cancer (8.68) and traumatic brain injury (8.46). Mental health and central nervous system disorders in general were weighted highly. There was a strong consistency in responses, reflected in the 95% confidence intervals and 0.20 average coefficient of variation. There was a positive correlation coefficient of 0.62 for Irish and GBD weightings placed in rank order. The correlation coefficient increased to a strongly positive 0.70 when outliers were omitted. A sensitivity analysis for input by gender showed only a 3.5% variation in average scores across all diseases and disabilities. Conclusion: Participants in our survey weighed diseases and disabilities consistently. The ranking of conditions also aligns with the findings of the most recent GBD study, supporting the universality hypothesis. The results highlight how different populations share a common perception of health conditions that transcends race, income and birthplace. These findings on consistency and relative ranking can inform policy makers and healthcare managers in the creation of health education and information programmes.